Distribution, eco-climatic characterisation, and potential growing regions of Annona cherimola Mill. (Annonaceae) in Mexico. - Rodríguez-Núñez, Jesús Rubén; Campos-Rojas, Eduardo; Andrés-Agustín, Jorge; Alia-Tejacal, Iran; Ortega-Acosta, Santo Angel; Peña-Caballero, Vicente; Madera-Santana, Tomás Jesús; Núñez-Colín, Carlos Alberto (Ethnobiology and Conservation, 2021)
The cherimoya (Annona cherimola Mill.) is a fruit crop with worldwide commercial importance. However, its distribution and potential growing regions of cherimoya are not defined for Mexico. That is why, this research aims to map the natural distribution of cherimoya and different eco-climatic regions where it is grown in Mexico as well as to map the climatic adaptability with the current climate and a prospection with the climate change scenario, all by different models of GIS. The general distribution model of cherimoya in Mexico showed that it had a chance to find cherimoya “in a natural way” in the biogeographic provinces Trans-Mexican Volcanic Belt, Sierra Madre del Sur and Highlands of Chiapas. Three eco-climatic groups were found in the distribution of cherimoya that corresponded to climates C(m)(w), (A)C(e’), and (A)C(e), respectively. Where the group with climate (A)C(e) had the most restricted distribution. The potential growing regions of excellent adaptation of cherimoya were found in the biogeographic provinces of Trans-Mexican Volcanic Belt, Sierra Madre Occidental, Sierra Madre Oriental, Sierra Madre del Sur and Highlands of Chiapas. Finally, based on eco-crop modelling, it is concluded that climate change will not greatly affect areas of excellent adaptation of cherimoya in Mexico.